Study and Control of Newcastle Disease in Ducks - Saepulloh, Muharam; ., Darminto (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
A study on the infection of Newcastle disease (ND) in ducks has been conducted at some areas in Indonesia and other countries by serology method and viral isolation. The result indicated that ND virus was capable of infecting ducks, stimulated immune response, with or without manifestation of the clinical signs of ND . Based on the pathotyping tests, viral isolates were considered as velogenic strains. Some infected ducks could spread the virus to the environment through faeces, so that it will be very dangerous for chicken breeder residing in the same location with many duck populations . On that account, ducks have an important role in spreading the ND virus, thus care should be taken on the presence of ducks in the poultry farms . Key word : Newcastle disease, ducks, velogenic strain